Advancing research, policy, and capacity for food system transformation synthesis of achievements from the Feed the Future Innovation Lab for Food Security Policy - Resnick, Danielle; Haggblade, Steven; Benson, Todd; Crawford, Eric (Michigan State University, 2019)
This paper reviews FSP’s achievements from 2013 to 2018 and discusses some of the key lessons learned while also documenting the project’s vast range of publications, presentations, policy briefs, and other outputs. FSP aimed to strengthen food security policy through three mutually reinforcing mechanisms. First, research drawing on survey data and primary fieldwork in diverse locations has contributed empirical content on frontier issues related to agri-food system and nutrition transformation, especially in an era of rapid urbanization, climatic shocks, and technological innovations. Novel findings emerged in areas such as diet change, post-farm processing and distribution, and land and labor markets. Second, by developing a strong conceptual understanding of the drivers of policy change in local policy processes, FSP pursued diverse forms of engagement with policymakers to influence outcomes ranging from rice policy in Myanmar to coffee prices in Rwanda to produce cess rates in Tanzania. Third, FSP provided a natural lab for experiments in building capacity for policy research, with a variety of approaches pursued in different country settings and targeting different audiences. These approaches included strengthening university networks for policy research and dialogue, partnering with independent or quasi-independent policy analysis institutes and think tanks, and implementing various forms of training for a broad range of stakeholders to strengthen capacity for policy research and dialogue.